Blind sports' blind spot: The global epidemiology of visual impairment against participation trends in elite blind para sport. (17th August 2022) - Stratton, Catherine S M; Fagher, Kristina; Li, Xiang; Ottesen, Taylor D; Tuakli-Wosornu, Yetsa A
Background: It remains unknown whether access to elite blind sports opportunities is globally balanced or matches the prevalence of blindness/visual impairment (VI). The primary objective of this study was to determine the rate of elite blind sports participation in each world region registered in the International Blind Sports Federation's (IBSA) and to assess its association with the global and regional prevalence of blindness/VI. The secondary objective was to determine the association between other covariates, such as age, vision class, and sex, with the number of IBSA-registered athletes from each region. Methods: A baseline estimate of blindness/VI data was established and used when comparing participation rates to blindness/VI rates. Descriptive statistics were used to describe sports participation and associated co-variates. Results: Among 123 member countries registered in IBSA, 31 did not have any completed registrations in blind sports, of which 22 had a prevalence of blindness/VI higher than the global average. During the summer season 2019, 738 (29.52%) IBSA athletes were female and 1762 (70.48%) were male. Conclusions: These results suggest elite blind/VI sport participation is limited independently from blindness/VI prevalence. Increasing blind-friendly sport resources, especially in low-and-middle-income countries (LMICs), would improve the rate of elite sport participation among athletes with blindness/VI.